In vitro cultures of Aquilaria malaccensis for agarwood production - Chiu, Sara Jane Soo Hoon (2016)
This thesis describes the results of a series of plant tissue culture, chemical and molecular based experiments aimed at developing an in vitro system to study the fundamental changes in chemical composition or activation of specific chemical pathways which take place during the onset and production of agarwood in Aquilaria malaccensis.